Syntrophic association of a butyrate-degrading bacterium and methanosarcina enriched from bovine rumen fluid. - McInerney, M J (1981)
An anaerobic butyrate-degrading bacterium, morphologically similar to Syntrophomonas wolfei, was isolated in coculture with Desulfovibrio strain G11 from an enrichment of bovine rumen fluid. A Methanosarcina species was the major H2-using organism in the enrichment. The results are discussed in relationship to the absence of Methanospirillum hungatei, the H2-using methanogen usually found in association with S. wolfei, and the finding of Methanosarcina rather than Methanobrevibacter ruminantium as the major H2-using bacterium in the enrichments. The finding of butyrate degraders in the rumen suggests that, if the retention time of the rumen contents becomes more prolonged, butyrate and longer-chained fatty acids might be significantly degraded.